Novel mutation and RNA splice variant of fibroblast growth factor receptor 3 in multiple myeloma patients at diagnosis - S Soverini; C Terragna; N Testoni; D Ruggeri; P Tosi; E Zamagni; C Cellini; M Cavo; M Baccarani; S Tura; G Martinelli (Haematologica, 2002)
BACKGROUND AND OBJECTIVES: The karyotypically silent t(4;14)(p16.3;q32) translocation can be found in approximately 15-20% of multiple myeloma (MM) patients and results in the ectopic expression of fibroblast growth factor receptor 3 (FGFR3) from der4. Point mutations in specific FGFR3 domains can be found in the translocated allele, and have been recently proven to be oncogenic. These mutations produce a constitutively activated receptor, which shows dimerization and autophosphorylation even in the absence of ligand. We investigated the presence of FGFR3 expression and activating mutations in a series of newly diagnosed MM patients. DESIGN AND METHODS: We validated a new sensitive and specific Taqman real-time reverse-transcription polymerase-chain-reaction (RT-PCR) set up to evaluate FGFR3 mRNA expression, and applied it to 78 newly diagnosed patients; in positive cases, FGFR3 mRNA transcripts were sequenced. Fluorescence in situ hybridization (FISH) was done in 32 cases with sufficient material. RESULTS: Real-time RT-PCR revealed FGFR3 mRNA expression in 10/78 (13%) patients. In two cases, sequence analysis revealed novel FGFR3 mutations. In a patient with FISH evidence of the t(4;14), a CGC to TGC transition was detected in codon 248. In a patient without the t(4;14), three additional, abnormal-sized transcripts were detected, corresponding to truncated transcripts originating from cryptic splice donor sites located within exon 7. INTERPRETATION AND CONCLUSIONS: We describe a novel FGFR3 mutation (with a demonstrated deregulatory mechanism), as well as a case of alternative splicing in the absence of t(4;14), detected in newly diagnosed MM patients overexpressing FGFR3. This implies that FGFR3 mutation can occur at an early stage of myelomagenesis and even in the absence of the t(4;14).